Pengaruh Terapi Bermain Labirin Terhadap Konsentrasi Anak Tunagrahita Di Slb Negeri Autis Sumatera Utara - Adawiyah Harahap, Yuliatil; Sharfina, Dirayati; Idris, Syamsul; Cut Mala, Putri (Universitas Haji Sumatera Utara, 2025)
Concentration is the concentration of the soul's function on an object, for example a child is said to concentrate on a lesson if he can focus on what is being learned, by concentrating the child is not easily distracted from other problems beyond what he is studying. So concentration is one of the supporting aspects of students to achieve good performance. The purpose of this study was to determine the effect of labyrinth playing therapy on the concentration of mentally retarded children in the Autistic State SLB of North Sumatra. This research method uses a Pre-Experiment with One Group Pre-Post test design. The study population of mentally retarded children used a purposive sampling technique with a total of 15 people. Methods of data collection using observation sheets. The statistical test used is the Unpaired sample t-test. The results of this study note that there is a significant difference. The results of the unpaired sample t-test obtained the value before being given maze playing therapy, the average concentration value of the child was 26.46. And after being given labyrinth play therapy the average value of the child's concentration increased, namely 74.33. The p-value of 0.000 <0.05 means that there is an effect of labyrinth playing therapy on the concentration of mentally retarded children in the Autistic State SLB of North Sumatra. The conclusion of this study is that there is an effect of labyrinth playing therapy on the concentration of mentally retarded children in the North Sumatra Autistic SLB. So it is recommended that teachers are able to apply this therapy as an alternative in improving children's concentration and vision.